Reading academic text: awareness and experiences among University ESL learners - Noorizah Mohd. Noor (Penerbit UKM, 2006)
Studying in the university for the first time may involve a sudden change in the way of learning for most students. These initial experiences of higher education may have a profound effect on whether these students are able to successfully complete their course of studies. The review of literature on students’ approaches to learning has often described students as either deep or surface learners. A deep approach is associated with intrinsic motivation and a focus on understanding the meaning of the learning material. In contrast, a surface approach focuses on memorizing discrete items in isolation resulting in superficial understanding of the learning material. Although these studies have provided information on the different approaches in various contexts, little research has been conducted within an ESL context. Accordingly, through phenomenography, the aim of this paper is to describe the reading process of six ESL learners within a Malaysian educational context. Findings will reveal that there exist ‘variations’ or ‘qualitative differences’ in these ESL students’ approaches of reading an English academic expository text.